Reviewing of Published Studies on Health risk Management in Emergency and Disaster - Khankeh, Hamidreza; Mehraein Nazdik, Zahra (Archives of Men’s Health, 2021)
Background: The need for comprehensive and more serious management of disasters and, consequently, the need for knowledge and how to use it in order to reduce the risk of disasters has increased. The importance of this issue is such that in 2016, the World Health Organization launched a research network related to health risk management in disasters. Accordingly, this study was conducted to review articles published in the field of health in emergency and disaster. Methods: In this study, the narrative review method has been used. The accessible articles published in the field of health Risk Management (health EDRM) from 2000 to 2019 were reviewed. Databases including Web of Science, PubMed, Google Scholar, Science Direct, Scopus, Medline, Magiran and SID were used. 24 studies had the inclusion criteria that were selected and analyzed. Data analysis was a qualitative content analysis in the form of components of health risk management in emergency and disasters. Results: Among the 24 studies reviewed, 21 articles were in English and 3 articles were in Persian. In addition, most of these studies were published in 2019. The articles were analyzed and reported in the form of components and functions of health risk management in emergency and disasters, published in 2019 by the World Health Organization. Conclusion: Studies show that the focus of most studies is on policies, strategies and legislation, planning and coordination, and less attention is paid to the components of risk communication and health services. Also, there are many research gaps and it is suggested that more research be done with more precise guidance.